A 90-Day Repeated Oral Dose Toxicity Study of Alismatis Rhizoma Aqueous Extract in Rats - Lee, Mu-Jin; Jung, Ho-Kyung; Lee, Ki-Ho; Jang, Ji-Hun; Sim, Mi-Ok; Seong, Tea-Gyeong; Ahn, Byung-Kwan; Shon, Jin-Han; Ham, Seong-Ho; Cho, Hyun-Woo; Kim, Yong-Min; Park, Sung-Jin; et al. (Toxicological research (Seoul), 2019)
Alismatis rhizoma (AR), the dried rhizome of Alisma orientale (Sam.) Juzep, is a well-known, traditional medicine that is used for the various biological activities including as a diuretic, to lower cholesterol and as an anti-inflammatory agent. The present study was carried out to investigate the potential toxicity of the Alismatis rhizoma aqueous extract (ARAE) following 90-day repeated oral administration to Sprague-Dawley rats. ARAE was administered orally to male and female rats for 90 days at 0 (control), 500, 1,000 and 2,000 mg/kg/day ( n = 10 for male and female rats for each dose). Additional recovery groups from the control group and high dose group were observed for a 28-day recovery period. Chromatograms of ARAE detected main compounds with four peaks. Treatment-related effects including an increase in the red blood cells, hemoglobin, hematocrit, albumin, total protein, and urine volume were observed in males of the 2,000 mg/kg/day group ( p < 0.05). However, the diuretic effect of ARAE was considered, a major cause of hematological and serum biochemical changes. The oral no-observed-adverse-effect level (NOAEL) of the ARAE was > 2,000 mg/kg/day in both genders, and no target organs were identified.